Neural correlates of fluctuations in the intermediate band for heart rate and respiration are related to interoceptive perception. (10th May 2020) - Keller, Micha; Pelz, Holger; Perlitz, Volker; Zweerings, Jana; Röcher, Erik; Baqapuri, Halim Ibrahim; Mathiak, Klaus
Abstract: Supratentorial brain structures such as the insula and the cingulate cortex modulate the autonomic nervous system (ANS). The neural underpinnings of separate frequency bands for variability in cardiac and respiratory data have been suggested in explaining parasympathetic and sympathetic ANS modulation. As an extension, an intermediate (IM) band in peripheral physiology has been considered to reflect psychophysiological states during rest. Using functional magnetic resonance imaging (fMRI), we investigated the neural correlates associated with IM band variability in cardiac and respiratory rate and identified dissociable networks for LF, IM, and HF bands in both modalities. Cardiac and respiratory IM band fluctuations correlated with blood oxygen level‐dependent (BOLD) signal in the mid and posterior insula and the secondary somatosensory area, that is, regions related to interoceptive perception. These data suggest that in addition to the commonly considered LF and HF bands, other frequency components represent relevant physiological constituents. The IM band may be instrumental for assessment of the CNS‐ANS interaction. In particular, the relation between the IM band and interoception may be of physiological and clinical interest. Abstract : In addition to the commonly investigated low and high frequency bands of autonomic regulation, an intermediate (IM) band at 0.12–0.18 Hz, considered to reflect psychophysiological states during rest, may be of physiological and clinical interest. Cardiac and respiratory IM band fluctuations correlated with blood oxygen level‐dependent signal fluctuations in the insula and secondary somatosensory cortex and may be related to interoceptive perception.